O Largo da Gente Sergipana arquitetado sobre as águas do rio Sergipe: percepções do ambiente a partir de estudantes - Souza, Marcos Vinicius dos Santos (2022)
The interactions among human beings and environments are shaped by a fine line between the material and the immaterial, through the field of perception. The act of perceiving is not only linked to sight, but to all the senses of the human body, which can be awakened by elements that make this awakening possible. In this sense, this study aims at analyzing the cultural representations in the landscape of the Largo da Gente Sergipana, built over the waters of the Sergipe River in Aracaju, from the perception of the high school 1st grade students at Colégio Estadual Tobias Barreto. To support the philosophical development process of the research, in a greater proximity to the subjects involved, the Phenomenology of Perception was chosen, in which makes it possible to develop an understanding of the singularities that permeate the study. Regarding the type of research, this study is anchored in qualitative research, which supports a holistic approach to the collected information, allowing a more comprehensive interpretation. As for the technical procedures, action research was prioritized, which subsidized the activities developed with the group of students. To achieve the outlined objectives, the following procedures were carried out: bibliographic and documental survey; presentation of the project at the school (principals, teachers and students); dialogues with participating students; pedagogical workshops for the knowledge construction on the research topic with the involved students; visit to Largo da Gente Sergipana and Sergipe River; making of mind maps; construction of the E-book and documentary. The interpretation and analysis of the information in this research were based on Content Analysis, which is aligned with the aforementioned methodological approach, in order to carry out analysis and interpretations that are related to the reality researched and the results obtained. However, the educational technical production consists of the construction of an e-book and a documentary, capable of contributing as paradidactic resources to be used in the formal and non-formal educational spheres, in order to value Sergipe’s cultural and environmental contexts.